MicroRNAs in pancreatic cancer metabolism - Singh, Pankaj K. (2012)
Advances in understanding the biology of tumour progression and metastasis have clearly highlighted the importance of aberrant tumour metabolism, which supports not only the energy requirements but also the enormous biosynthetic needs of tumour cells. Such metabolic alterations modulate glucose, amino acid and fatty-acid-dependent metabolite bio-synthesis and energy production. Although much progress has been made in understanding the somatic mutations and expression genomics behind these alterations, the regulation of these processes by microRNAs (miRNAs) is only beginning to be appreciated. This Review focuses on the miRNAs that are potential regulators of the expression of genes whose protein products either directly regulate metabolic machinery or serve as master regulators, indirectly modulating the expression of metabolic enzymes. We focus particularly on miRNAs in pancreatic cancer.